Nuclear War Games poster, 1984
1986 1960-2000 "Nuclear War Games poster, 1984" [T0589.jpg], c. 1985 This poster was issued by several public sector unions and the Trade Union Campaign for Nuclear Disarmament campaigning against local government expenditure on civil defence. Several local authorities at that time declared themselves nuclear-free zone councils.